Comparison of Shear Bond Strength of Sapphire Bracket Bonded to Zirconium Surface after Using Different Surface Conditioning Methods (In Vitro Study) - Ihsan, Hawraa; AlDabagh, Dhiaa J (Journal of Baghdad College of Dentistry, 2017)
Background: The present study was carried out to compare shear bond strength of sapphire bracket bonded to zirconium surface after using different methods of surface conditioning and assessment of the adhesive remnant index.Materials and methods: The sample composed of 40 zirconium specimens divided into four groups; the first group was the control, the second group was conditioned by sandblast with aluminum oxide particle 50 Î¼m, the third and fourth group was treated by (Nd: YAG) laser (1064nm)(0.888 Watt for 5 seconds) for the 1st laser group and (0.444 Watt for 10 seconds) for the 2nd laser group. All samples were coated by z-prime plus primer. A central incisor sapphire bracket was bonded to all samples with light cure adhesive resin. Shear bond strength was measured by using Tinius Olsen universal testing machine. After debonding, each bracket and zirconium surface were examined and adhesive remnant index was registered. The difference in shear bond strength among groups was analyzed by using ANOVA test. The adhesive remnant index was assessed using Chi-square test.Results: The 2nd laser group had the highest mean value of shear bond strength then the 1st laser group followed by the sandblasting group, while the control group had the least value, non-significant difference in the shear bond strength was found between the laser groups and highly significant difference was found between all other comparable groups. Non-significant difference in the site of bond failure was found between the laser groups and sandblasting group, and between the two laser groups.Conclusion: The laser conditioning method showed higher value of shear bond strength than the sandblasting conditioning method.